Mechanisms that stabilize human walking - van Leeuwen, Moira; Bruijn, Sjoerd; van Dieën, Jaap (Brazilian Journal of Motor Behavior, 2022)
In this paper we review what mechanisms are used to stabilize human bipedal gait. Based on mechanical reasoning, potential mechanisms to control the body center of mass trajectory are modulation of foot placement, stance leg control consisting of modulation of ankle moments and push-off forces, and modulations of the body’s angular momentum. The first two mechanisms and especially the first are dominant in controlling center of mass accelerations during gait, while angular momentum control plays a lesser role, but may be important to control body alignment and orientation. The same control mechanisms stabilize both steady-state and perturbed gait in both the mediolateral and antero-posterior directions. Control is at least in part active and is affected by proprioceptive, visual and vestibular information. Results support that this reflects a feedback process in which sensory information is used to obtain an estimate of the center of mass state based on which foot placement and ankle moments are modulated. These active feedback mechanisms suggest training approaches for populations at risk of falling, such as augmenting their effective use by means of augmented feedback, or using their complementary nature to train one mechanism by constraining the other mechanisms.